Recent Development of Municipal Finance in Selected European Countries - Peter Friedrich; Anita Kaltschütz; Chang Woon Nam (European Regional Science Association (ERSA), 2004)
The idea of fiscal decentralisation has become increasingly fashionable world-wide. In some developed countries the systems of intergovernmental finance have evolved gradually and each country has unique features. Transition countries on different continents have had differing reasons and motivations for such reforms. More recently, the acknowledgement of subsidiarity as the basic principle for the European Un-ion, the introduction of the West German federal system in the eastern part of the country, the revival of regionalism in European countries are distinctive examples of the decentralisation process in Europe. Following the equalisation objectives, one tends to argue that those municipalities with greater spending needs automatically require more financial support from central or upper-level government. Yet, the sum of grants to municipalities should basically be induced from the comparison of their expenditure needs with local fiscal capacity from their own resources such as local tax revenues and fees. Surely the expenditure behaviour of municipalities is also, to a great extent, influenced by their present fiscal capacity and by the size of local debts. Four European countries were chosen to survey the recent development of local finance: the UK, Germany, Poland and Switzerland. This paper firstly identifies and highlights the similarities and differences in municipal finance in an international context. Secondly it theoretically examines the possibility of enhancing fiscal autonomy of local governments through increasing revenues from fees. Keywords: fiscal decentralisation, local expenditures and taxes, shared taxes, intergovernmental transfers, municipal borrowings, Poland, the UK, Switzerland, Germany
Keywords: 330; fiscal decentralisation; local expenditures and taxes; shared taxes; intergovernmental transfers; municipal borrowings; Poland; the UK; Switzerland; Germany